Child rights and protection in slum settlements of Kampala, Uganda: A qualitative study. Issue 3 (27th May 2018) - Renzaho, Andre M. N.; Kamara, Joseph Kihika; Stout, Brian; Kamanga, Gilbert
ABSTRACT: Child abuse and neglect are complex and polarizing issues in many low and middle income countries. We explore them through a situation analysis of child rights and protection in Uganda. A qualitative study, incorporating 10 focus group discussions (FGDs; N = 113) and 20 individual interviews was undertaken in Kampala, Uganda. Emerging themes were grouped into family and community-level factors; legal framework, structure and continuum of services, and human and financial resources. Violation of child rights was characterized by physical, emotional, and sexual abuse and exploitation; child neglect, homelessness, and child labor; dysfunctional families and abject poverty; and poor accommodation conditions; school drop-out due to economic hardship; early pregnancy, and social exclusion. Legal and regulatory factors included traditional harmful practices (including child sacrifice and witchcraft practices); forced marriage; and the perceived lack of the government's commitment to child protection. Without a strong legislation that protects children against abuse, promotes confidential reporting systems, and tackles domestic violence, children will still remain prone to various forms of abuses and exploitation.